Humanising The 'Naire' in Money: A Scoping Review - Olutayo, Lanre Akinpelu Olanrewaju; Oyenuga, Adedeji Saheed (Journal of Applied And Theoretical Social Sciences, 2024)
As the world progresses into the critical Year 2030, the magic Year for attaining the Sustainable Development Goals, doubts about the certainty of success are high. Amid COVID-19, the climate crisis, the Russia-Ukraine war, among many other wars, and the high cost of living pushing most of the people into poverty and hardship, it is time to reconsider what is being done to make the world a better place for most of the people. In doing this, this paper attempts to interrogate the influence of money in the consistent world economic crises. It argues that the 'inevitability of money', attendant on changing technology, pervading the World Capitalist System needs to be reoriented to homos sociologicus. In a way, it recommends the need to 'humanise' money and technology, such that humans construct it socially instead of vice versa.